2014
DOI: 10.3989/scimar.03929.06b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-borne copper on the survival, antioxidant status, metallothionein-I mRNA expression and physiological responses of the Chinese mitten crab, <em>Eriocheir sinensis</em> (Decapoda: Brachyura) larvae

Abstract: Summary:The lethal concentration of water-borne copper in Chinese mitten crab Eriocheir sinensis larvae was tested by exposing the animals to 0, 0.1, 0.2, 0.3, 0.5 and 0.8 mg Cu L −1 at 20°C for 96 h. The 96-h median lethal concentration (LC 50 ) and its corresponding 95% confident interval was estimated on zoea 1 larvae and megalopa larvae, respectively. Acute dissolved copper toxicity was higher for zoea 1 larvae (0.16 mg L -1 ) than for megalopa larvae (0.21 mg L -1 ). The antioxidant status, metallothione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The dose dependent alteration of SOD, CAT, LPO, GOT, and GPT has been reported in M. rosenbergii fed to Cu supplemented diets [13]. Also, Sun et al [41] reported that the insufficient or excess level of dietary Cu produced depressed hepatic SOD, TBARS and GPx activity in the crab, E. sinensis. The sea anemone, Exaiptasia pallid sowed elevated CAT level when exposed to high level of water borne Cu and CuO-NPs [43].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The dose dependent alteration of SOD, CAT, LPO, GOT, and GPT has been reported in M. rosenbergii fed to Cu supplemented diets [13]. Also, Sun et al [41] reported that the insufficient or excess level of dietary Cu produced depressed hepatic SOD, TBARS and GPx activity in the crab, E. sinensis. The sea anemone, Exaiptasia pallid sowed elevated CAT level when exposed to high level of water borne Cu and CuO-NPs [43].…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that the Cu-NPs have influenced the production of haemocyte population in experimental prawns. Similarly, dietary Cu supplemented feed fed P. monodon and E. sinensis shown significant elevations in THC and intracellular superoxide anion (O 2 − ) production ratio [7,9,41]. Cu supplemented feed fed H. discus hannai produced better performance in phenol oxidase and lysozyme activity [7].…”
Section: Discussionmentioning
confidence: 96%
“…High ambient Cu 2+ is a significant threat to the health of E. sinensis. After 24 h of Cu 2+ exposure, the metabolism and osmotic regulation in the gills of E. sinensis are altered [ 21 ], and after 96 h, its molting, growth, and survival are suppressed [ 22 , 23 ]. Although Cu 2+ toxicity in E. sinensis has garnered much attention in recent years, the knowledge of its underlying molecular mechanisms remains limited.…”
Section: Introductionmentioning
confidence: 99%